Evaluation of Asymmetric Dimethylarginine Levels in Patients With Chronic Thromboembolic Pulmonary Hypertension Undergoing Pulmonary Endarterectomy - YILDIZELİ, BEDRETTİN (Elsevier Ltd, 2022)
Background: Chronic thromboembolic pulmonary hypertension (CTEPH) is a form of pulmonary embolism, and pulmonary endarterectomy (PEA) is the surgical treatment. Asymmetric dimethylarginine (ADMA) levels are increased in pulmonary hypertension. This study aimed to investigate serum ADMA levels in patients with CTEPH, the effect of PEA on ADMA, and its prognostic value in long-term mortality. Method: Eighty (80) patients with CTEPH and 32 healthy controls were included. Preoperative serum ADMA levels, determined using an enzyme-linked immunosorbent assay, were compared between patients with CTEPH and controls. Of 80 patients, 64 had PEA. Pre- and 6-month postoperative serum ADMA levels, 6-minute walk distance (6MWD), and haemodynamic parameters were collected from patients undergoing PEA. Patients were followed-up for survival analysis. Results: Mean ± standard deviation serum ADMA levels were significantly higher in patients with CTEPH compared with controls (0.79±0.32 μmol/L vs 0.52±0.12 μmol/L; p=0.0001). Statistically significant differences were observed between preoperative and postoperative serum ADMA levels (0.78±0.30 μmol/L vs 0.62±0.22 μmol/L; p=0.0001), 6MWD (p=0.0001), and pulmonary vascular resistance (p=0.0001) in 60 patients who underwent and survived PEA. The decrease in serum ADMA levels and increase in 6MWD were significantly correlated (r=–0.286, p=0.027). No other correlation was found. Perioperative mortality was 6.3%, and the survival rate with a mean follow-up of 34.57±8.20 months was 93.3%. Patients with serum ADMA levels >0.8 μmol/L had a significantly lower survival rate (logrank: 5.86; p=0.015). Conclusions: Levels of circulating ADMA might add diagnostic and prognostic information in CTEPH. Pulmonary endarterectomy is associated with an improvement in serum ADMA levels. Preoperative serum ADMA levels may be useful for estimating the outcome of PEA. © 2021 Australian and New Zealand Society of Cardiac and Thoracic Surgeons (ANZSCTS) and the Cardiac Society of Australia and New Zealand (CSANZ)
Keywords: Asymmetric dimethylarginine; Chronic thromboembolic pulmonary hypertension; Pulmonary endarterectomy